P16-positive senescent cells promote DKD by the dysregulation of glycolysis and mitochondrial metabolism - Xiao Lu; Jiao Wu; Ewud Agborbesong; Xiaogang Li (Cell Death Discovery)
Abstract Diabetic kidney disease (DKD) is characterized by kidney damage and abnormal renal energy metabolism, but the molecular mechanism of DKD is still unclear. In this study, we show that p16- positive senescent cells are an important regulator in the progression of DKD. The expression of p16 and senescence are increased in the kidneys of DM mice and DKD patients. To better understand the role of p16 in DKD, we induce type 1 diabetes in INK-ATTAC mice, a mouse model that allows the selective ablation of p16-expressing cells upon administration of the drug AP20187. We found that clearance of p16-positive cells, most of them are senescent cells, (1) decreased senescence and the expression of the components of the senescence-associated secretory phenotypes (SASPs), (2) restored kidney adenosine triphosphate (ATP) content, (3) decreased the expression of the key glycolytic genes to improve the metabolic reprogramming, (4) normalized the mitochondrial metabolism through AMPK and mTOR pathway, resulting in an amelioration of the progression of DKD. In addition, p16 mediated the blocking of the cell cycle is through the CDK4-Rb pathway in DKD kidneys. This study suggests that pharmacological deletion of p16-positive senescent cells may be a novel therapeutic strategy for DKD treatment.